2011
DOI: 10.1007/s10389-011-0445-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exclusive consumption of fluoride-free water: a cross-sectional household study in rural Ethiopia

Abstract: Aim The occurrence of high fluoride concentrations in the ground-and surface water all over the world leads to the risk of developing dental and skeletal fluorosis. In Ethiopia, 8 million people depend on water sources with excessive fluoride. In four project areas in the Ethiopian Rift Valley, fluoride removal household filters based on bone char media have been implemented. This study examines possible predictors of consuming filtered water derived from various behavior change theories. Subject and methods I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
(28 reference statements)
4
29
0
Order By: Relevance
“…The present study provides insights into people’s acceptance. Importantly, in line with previous research on safe water consumption [31], [32], it was shown that the RANAS factors reliably differentiate between users and non-users of arsenic-safe water options. In the following, we will discuss the psychological factors that were found favorable or unfavorable for the acceptance of each safe water option (Table 4), as well as possible interventions to increase acceptance.…”
Section: Discussionsupporting
confidence: 83%
“…The present study provides insights into people’s acceptance. Importantly, in line with previous research on safe water consumption [31], [32], it was shown that the RANAS factors reliably differentiate between users and non-users of arsenic-safe water options. In the following, we will discuss the psychological factors that were found favorable or unfavorable for the acceptance of each safe water option (Table 4), as well as possible interventions to increase acceptance.…”
Section: Discussionsupporting
confidence: 83%
“…These studies further revealed the importance of commitment to the use of safe water (Inauen and Mosler, 2013;Inauen et al, 2013c). In summary, in line with previous research on safe water consumption (Huber et al, 2012;Huber and Mosler, 2013;Kraemer and Mosler, 2012;Tamas and Mosler, 2011;Tobias and Berg, 2011) these studies indicate that more committed persons, who perceive safe water collection as more typical, have higher confidence in their abilities to collect safe water, find safe water collection less time consuming and effortful, and who perceive more approval from others to collect arsenic-safe water are more likely to use arsenicsafe water options.…”
Section: Psychological Aspectssupporting
confidence: 86%
“…Most of the questionnaire items were derived from the RANAS approach (Mosler, 2012) and previous studies (Contzen & Mosler, 2013;Huber et al, 2012;. Some of the factors of the RANAS were measured both regarding stool-and food-related handwashing separately (see below).…”
Section: Methodsmentioning
confidence: 99%